The Influence of Managerial Competence and Employee Discipline on Public Service Quality at the Education and Culture Office of Banyuasin Regency - Arifin Suradilaga; Rohana; Tri Widayatsih (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aimed to analyze the influence of managerial competence and employee discipline on public service quality at the Education and Culture Office of Banyuasin Regency. The study employed a quantitative approach with a correlational design. The population comprised 167 employees, and 118 respondents were selected using the Slovin formula at a 5% margin of error and proportionally allocated across seven divisions or work units. Data were collected through Likert-scale questionnaires, documentation, and guided observation. The managerial competence, employee discipline, and public service quality instruments obtained Cronbach's Alpha coefficients of 0.946, 0.969, and 0.975, respectively. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, t-tests, an F-test, and the coefficient of determination with SPSS version 26. The results showed that managerial competence had a positive and significant influence on public service quality (B = 0.308; t = 2.585; p = 0.011). Employee discipline had a positive direction of influence but was not partially significant (B = 0.079; t = 0.713; p = 0.477). Simultaneously, managerial competence and employee discipline significantly influenced public service quality (F = 3.825; p = 0.025), with an R² of 0.062. These findings indicate that improving public service quality requires prioritizing stronger managerial competence while maintaining work discipline within a more integrated service system.